BANΔIT: B'‐Factor Analysis for Drug Design and Structural Biology. Issue 1 (6th September 2020) - Barthels, Fabian; Schirmeister, Tanja; Kersten, Christian
Abstract: The analysis of B‐factor profiles from X‐ray protein structures can be utilized for structure‐based drug design since protein mobility changes have been associated with the quality of protein‐ligand interactions. With the BANΔIT (B'‐factor analysis and ΔB' interpretation toolkit), we have developed a JavaScript‐based browser application that provides a graphical user interface for the normalization and analysis of B'‐factor profiles. To emphasize the usability for rational drug design applications, we have analyzed a selection of crystallographic protein‐ligand complexes and have given exemplary conclusions for further drug optimization including the development of a B'‐factor‐supported pharmacophore model for SARS CoV‐2 main protease inhibitors. BANΔIT is available online at https://bandit.uni‐mainz.de. The source code can be downloaded from https://github.com/FBarthels/BANDIT. Abstract :